Characterizing scale‐dependent community assembly using the functional‐diversity–area relationship. Issue 11 (1st November 2013) - Smith, Adam B.; Sandel, Brody; Kraft, Nathan J. B.; Carey, Susan
Abstract : Phenotypic traits mediate organisms' interactions with the environment and determine how they affect and are affected by their biotic and abiotic milieu. Thus, dispersion of trait values, or functional diversity (FD) of a community can offer insights into processes driving community assembly. For example, underdispersion of FD suggests that habitat "filtering" of species with unfavorable trait values restricts the species that can exist in a particular habitat, while even spacing of FD suggests that interspecific competition, or biotic "sorting, " discourages the coexistence of species with similar trait values. Since assembly processes are expected to vary as a function of spatial scale, we should also expect patterns of FD to reflect scale dependence in filtering and biotic sorting. Here we present the concept of the functional‐diversity–area relationship (FAR), which is similar to the species–area relationship but plots a measure of phenotypic trait diversity as a function of spatial scale. We develop a set of null model tests that discriminate between FARs generated predominantly by filtering or biotic sorting and indicate the scales at which these effects are pronounced. The utility of the FAR for addressing long‐standing issues in ecology is illustrated with several examples. A multi‐scale examination of FD and its pattern relative to null expectations provides an important tool for ecologists interested in understanding the scale dependence of community assembly processes.